To study the anatomical variations at saphenofemoral junction in varicose veins - Sunil Kumar Yadav; Madan Gopal Vashist; Akshay P Marak; Naresh Pal; Rahul Kumar; Kushagra Bansal (Asian Journal of Medical Sciences, 2025)
Background: Varicose veins are a common vascular condition affecting a significant proportion of the adult population and can cause symptoms ranging from cosmetic concerns to pain, edema, and ulceration. One of the primary anatomical sites of interest in varicose vein pathology is the saphenofemoral junction (SFJ), where reflux often originates. Understanding the anatomical variations of the SFJ is crucial for accurate diagnosis, effective surgical intervention, and minimizing post-operative recurrence. Duplex ultrasonography is a key diagnostic tool for assessing venous competence and identifying anatomical variations, but discrepancies between pre-operative imaging and intraoperative findings can impact surgical outcomes. Aims and Objectives: This study aims to investigate the anatomical variations at the SFJ, compare pre-operative duplex ultrasonography findings with intraoperative observations, and examine variations in tributaries in patients with primary varicose veins. Materials and Methods: A prospective study was conducted with 50 patients undergoing surgery for varicose veins. Clinical examinations and venous duplex ultrasound (USG) were used to assess the location and condition of the SFJ, with findings being compared to intraoperative results. Results: Results showed that SFJ was found to be incompetent in all patients, with 52% having superficial vein incompetence saphenopopliteal junction and 94% displaying perforator incompetence. The mean location of SFJ was found to be 2.5 cm inferior and 3.6 cm lateral to the pubic tubercle on pre-operative duplex USG, with similar findings observed intraoperatively (2.6 cm inferior, 3.7 cm lateral). The number of tributaries ranged from 1 to 5, with a mean of 3.04 tributaries. External pudendal artery was found posterior to SFJ in 90% of patients. Conclusion: The study highlights that pre-operative duplex USG is accurate in locating the SFJ and that a precise understanding of anatomical variations at the SFJ is essential to reduce recurrence of varicose veins. This research underlines the importance of identifying all tributaries and variations during surgery to ensure complete ligation and successful outcomes.